SMART TROLLY DESIGN BASED ON MARKER DETECTION - Syahrul Nugraha Trisno; Achmad Ubaidillah; Kunto Aji Wibisono (Universitas Muhammadiyah Ponorogo, 2021)
In this modern era, robots are very instrumental in helping the human work and even replace their work. From the various human works, humans will need a trolley to carry goods. As in supermarkets, people will need a trolley to make it easier to carry groceries and other luggage. But with a trolley that is commonly used, users must encourage the trolley to move so that it reduces hand activity to do other activities. Therefore, we need a trolley that can move to follow the user automatically, so the user no longer needs to push the trolley, and the user's hand can be more free to do other activities. This research discusses about trolley robot using marker detection. With the application of this method will help the robot determine the object so as to facilitate the movement of the robot to follow the user. In the testing process carried out in the study, the system accuracy in detecting markers on objects was 70%.